To pay or not to pay: Measuring risk preferences in lab and field - Brañas-Garza, Pablo; Estepa-Mohedano, Lorenzo; Jorrat, Diego; Orozco, Victor; Rascón-Ramírez, Ericka (Judgment and decision making, 2021)
Measuring risk preferences using monetary incentives is costly. In the field, it might be also unfair and unsafe. The commonly used measure of Holt and Laury (2002) relies on a dozen lottery choices and payments, which make it time consuming and expensive. It also raises moral concerns as a result of the unequal payments generated by good and bad luck. Paying some but not all subjects may also create tensions between the researcher and subjects. In a pre-registered study in Honduras, Nigeria and Spain, we use a short version of Holt and Laury where we address all three concerns. We find in the field that not paying at all or paying with and without probabilistic rules makes no difference. Our hypothetical and short version makes our measurement of risk cheaper, fairer and safer.